Winning space for conservation: the growth of wildlife conservancies in Kenya - Bashir, Munira Anyonge; Wanyonyi, Edwin (Frontiers in Conservation Science, 2024)
Kenya's conservation areas consist of national parks and reserves, national forests, private and community wildlife conservancies. The historical protected areas only account for 10% of Kenya's land mass (national parks, reserves, and protected forests). Conserving Kenya's biodiversity referred to as a 'national heritage' is at the core of the country's conservation agenda. The success of Kenya's model of free-ranging wildlife is based on allowing as much unhindered movement and distribution of wildlife as possible. However, human population increase, along with the expansion of agriculture into arid lands and the impacts of climate change, has affected the dynamics of pastoralism, where increased competition for natural resources has escalated in some areas. One of the identified measures to mitigate the current challenges is to increase the space for conservation and provide incentives for communities to conserve. The development and growth of the wildlife conservancy movement in Kenya has been a prominent response. As at 2023, there were 230 wildlife conservancies in Kenya totaling 9.04 million ha and comprising 16% of Kenya's total land mass (with 190 being members of Kenya Wildlife Conservancies Association). In order to contribute to the global target of protecting 30% of lands, freshwaters and oceans by 2030, the Kenyan Government considers the expansion of the number and area of wildlife conservancies as an important mechanism to contribute to these targets. Here we discuss Kenya's wildlife conservancies from legal and policy perspective, the factors that have enabled their growth, the challenges they face and the opportunities ahead.